Quality of interactive media use in early childhood and child development: a multicriteria analysis - Juliana N.P. Nobre; Bernat Vinolas Prat; Juliana N. Santos; Lívia R. Santos; Leiziane Pereira; Sabrina da C. Guedes; Rayane F. Ribeiro; Rosane Luzia de S. Morais (Elsevier, 2020)
Objectives: (1) To develop an index that allows the measurement of the quality of interactive media used by children in early childhood. (2) To verify whether there is an association between the index and cognitive development, expressive language, and fine and gross motor development. Methods: A quantitative, cross-sectional, exploratory study with 103 children, aged 24 to 42 months, evaluated by the Bayley Scale of Infant and Toddler Development. The criteria for the index were selected from the literature: (1) media use by parents; (2) time of daily media use; (3) media type; (4) what do you use the media for; (5) who do you use the media with (6) monitoring (limits time, content, interacts during use); (7) purpose of use; (8) parents' opinion of the media. For development of the multicriteria index, the multi-attribute utility theory was applied, and Spearman correlation and simple linear regression (p < 0.05) were used to verify the association between the index and child development. Results: The index showed a positive and significant correlation with child development in the following domains: language (r = 0.40, p < 0.001), cognitive (r = 0.23, p = 0.04), and fine motor = 0.22, p = 0.04). Simple linear regression analysis showed that the use of interactive media accounts for 22% of language development (p < 0.001). Conclusion: The multicriteria index developed to verify the quality of interactive media used by children in early childhood showed that it has the potential to be used. The positive and significant associations between the quality of interactive media use and child development was verified, mainly regarding language. Resumo: Objetivos: (1) Elaborar um índice que possibilite mensurar a qualidade de uso de mídias interativas por crianças na primeira infância. (2) Verificar se há relação entre o índice e o desenvolvimento cognitivo, linguagem expressiva, motor fino e grosso. Métodos: Estudo quantitativo, transversal, exploratório, com 103 crianças de 24 a 42 meses avaliadas pela Bayley Scale of Infant and Toddler Development. Os critérios para o índice foram selecionados a partir da literatura: (1) uso de mídias pelos pais; (2) tempo de uso de mídia/dia; (3) tipo de mídia; (4) para que usa a mídia; (5) com quem usa a mídia (6) acompanhamento dos pais (limita tempo, conteúdo, interage durante); (7) objetivo do uso; (8) opinião dos pais sobre a mídia. Para a elaboração do índice multicritério foi aplicado o Multi-Attribute Utility Theory e para verificar a relação entre o índice e o desenvolvimento infantil a análise de Correlação de Spearman e Regressão Linear Simples (p ˂ 0,05). Resultados: O índice apresentou correlação positiva e significativa com o desenvolvimento infantil nos domínios: linguagem (r = 0,40, p < 0,001), cognitivo (r = 0,23, p = 0,04), motor fino (r = 0,22, p = 0,04). A análise de regressão linear simples demonstrou que o uso de mídias interativas explica 20% do desenvolvimento da linguagem (p < 0,001). Conclusão: O índice multicritério elaborado para verificar a qualidade das mídias interativas em crianças na primeira infância mostrou ter potencial para aplicação. Constatou-se a relação positiva e significativa entre a qualidade de uso de mídias interativas e o desenvolvimento infantil, principalmente para a linguagem.